Integrating RNAi Technology in Smallholder Farming: Accelerating Sustainable Development Goals - Willow, Jonathan; Veromann, Eve (Frontiers in Sustainable Food Systems, 2022)
Approximately 84% of farms globally are <2 hectares; these and other smallholder farms collectively produce over one third of humanity's food. However, smallholder farms, particularly in developing countries, encounter difficulties in both production and profits due to their vulnerabilities. Sustainable intensification—increasing crop yield without significantly greater resource use—must be globally adopted in smallholder farming to achieve various Sustainable Development Goals (SDGs) endorsed by the United Nations (UN). While traditional techniques for conservation agriculture must be maintained and further promoted, new technologies will undoubtedly play a major role in achieving high yields in a sustainable and environmentally safe manner. RNA interference (RNAi) technology, particularly the use of transgenic RNAi cultivars and/or sprayable double-stranded RNA (dsRNA) pesticides, could accelerate progress in reaching these goals due to dsRNA's nucleotide sequence-specific mode of action against eukaryotic and viral pests. This sequence-specificity allows silencing of specific genetic targets in focal pest species of interest, potentially resulting in negligible effects on non-target organisms inhabiting the agroecosystem. It is our perspective that recent progress in RNAi technology, together with the UN's endorsement of SDGs that promote support in- and for developing countries, should facilitate an integrated approach to sustainable intensification of smallholder farms, whereby RNAi technology is used in combination with traditional techniques for sustainable intensification. However, the development of such approaches in developing countries will require developed countries to adhere to currently-defined socioeconomic SDGs.